2011
DOI: 10.1007/s00701-011-1133-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a multiple system atrophy model in rats using multitracer microPET

Abstract: Pathological changes consistent with MSA-p can be generated by the double toxin-double lesion method and persist during follow-up. Behavioral tests, such as drug-induced rotation and rotarod tests, are not appropriate for long-term follow-up in the MSA-p model, suggesting the need for development of more appropriate behavioral tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…This imaging method can diagnose the state of PD more precisely than behavior tests. [ 18 F]-FP-CIT microPET images were useful and consistent indicators of movement disorders in a rat model in our previous reports 29 , 30) . In this study, there was a significant increase in [ 18 F]-FP-CIT uptake by 10 weeks posttransplantation compared to the pretransplantation state.…”
Section: Discussionsupporting
confidence: 72%
“…This imaging method can diagnose the state of PD more precisely than behavior tests. [ 18 F]-FP-CIT microPET images were useful and consistent indicators of movement disorders in a rat model in our previous reports 29 , 30) . In this study, there was a significant increase in [ 18 F]-FP-CIT uptake by 10 weeks posttransplantation compared to the pretransplantation state.…”
Section: Discussionsupporting
confidence: 72%
“…In previous studies, the apomorphine-induced rotation test revealed an increase in contralateral rotations after injection of 6-OHDA into the MFB, and a decrease in contralateral rotations after subsequent injection of QA into the ipsilateral striatum ( 12 , 24 ). However, the decrease in contralateral rotations after injection of QA into the striatum can spontaneously recover without any treatment ( 12 , 24 ). The mechanism underlying this spontaneous recovery after sequential double toxin-double lesion is not clear, but it is possible that the QA-induced lesion in the striatum was insufficient to generate persistent rotation behavior ( 24 ).…”
Section: Discussionmentioning
confidence: 81%
“…We have introduced a multitracer microPET evaluation to clarify the exact status of SND during long term follow-up ( 12 ). MicroPET scanning is a non-invasive imaging method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Behavior tests including rotarod, beam, and air-righting reflex tests have been used to objectively determine balance in a mouse model of vestibular disorder [5, 6]. The rotarod test is also used to determine balance and coordinate movement in mice with central nervous disorders including cerebellar ataxia [7], multiple system atrophy (MSA) [8], and parkinsonism [9]. To our knowledge, however, there is no information about impaired cVEMP in a mouse model of vestibular disorder, while only three previous studies have succeeded in showing impairments of cVEMP in guinea pigs treated with gentamicin [1012].…”
Section: Introductionmentioning
confidence: 99%